Detection of recurrent phosphaturic mesenchymal tumors by using Ga-68 DOTATATE PET/CT - Ashfaq, Wardah; Iftıkhar, Iqra; Fayyaz, Mariam; Khızer, Mahnam; Fatıma, Saira; Younis, Muhammad Numaır (The European Research Journal, 2024)
Phosphaturic mesenchymal tumor is a rare clinical condition and often causes osteomalacia due to tumor. Its diagnosis is often significantly delayed due to its rare occurrence in addition to the generalized and vague symptoms of their presentation. A 19-year-old female with a history of left facial nerve palsy, generalized weakness and hoarseness of voice revealed a dense mass in her brain. In this case, we reported successful application of a Ga-68 labeled DOTATATE PET/CT scan to identify the primary site and distant metastases of phosphaturic mesenchymal tumors and show the diagnostic value of Ga-68 labeled DOTATATE PET/CT imaging for the rare tumors.